THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON STUDENTS' PHYSICS LEARNING OUTCOMES - Kurniawati, Kurniawati; Kakakios, Nikitas (EduFisika: Jurnal Pendidikan Fisika, 2024)
The purpose of this study is to measure student learning outcomes using problem-based learning models on students' physics learning outcomes. The research method is using experimental research. The research design used is Posttest-Only Control Design. The sampling technique used in the study was simple random sampling, so one class was obtained as a control class, namely class X mathematics science 2 and one class as an experimental class. With Data Analysis Techniques using Descriptive Analysis and inferential analysis. The results of the study showed that students who were taught with problem-based learning models had high average physics learning outcomes scores, while students who were not taught with this model had average physics learning outcomes scores that were in the low and sufficient categories. This study also found a significant difference in physics learning outcomes between the two groups, indicating that problem-based learning models have a positive effect on students' physics learning outcomes. This study provides a new perspective in measuring the effectiveness of problem-based learning models, especially in improving students' physics learning outcomes, which have not previously been widely studied in the context of physics learning in Indonesia.